Enhancing Early Childhood Educators’ Skills in Co-regulating Children’s Emotions: A Collaborative Learning Program - Mänty, Kristiina; Kinnunen, Susanna; Rinta-Homi, Outi; Koivuniemi, Marika (Frontiers in Education, 2022)
The aim of this article is to introduce a research-based work-integrated collaborative learning program that focuses on early childhood education and care (ECEC) professionals’ skills in co-regulation of emotions. The collaborative learning program draws on the theoretical framework that acknowledges the situated and socially shared nature of regulated learning and emotion regulation as well as years of research highlighting the importance of versatile and sensitive adults in supporting children’s learning of regulation skills during their early years. The program aims to improve professionals’ shared awareness of children’s emotion regulation development and abilities to identify and develop practices that support children in learning these skills, so that they can provide conscious and consistent co-regulation of emotions for children in everyday interactions. The design of the program has been developed by considering the aspects of effective collaborative and professional learning. This paper focuses on describing the theoretical grounding and implementation of a 32-week long collaborative learning program for ECEC professionals in Northern Finland (N = 450). Also, the development of a video-stimulated questionnaire (VSQ) for assessment of professionals’ learning during the program will be described. VSQ measures professionals’ abilities to identify and interpret everyday ECEC interactions from the point of view of (co-)regulation of emotions. Developing research-based collaborative programs that increase systematic support for children to learn regulation skills is essential, as these skills affect children’s lives well into adulthood. They set a basis for children’s learning and social skills and general wellbeing.